Model of Women Empowerment for Environmental Conservation - Deerada, Sasithorn (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (online), 2016)
The objective was to develop a model of women empowerment and psychological state affecting environmental conservation behavior through inspiration of public mind. The populations were 19,844 women committees of Maha Sarakham Province. The Multi-stage random sampling technique was employed to collect the sample of 400 women committees from different district and sub-district of Maha Sarakham Province. Questionnaire was used for data collection. Structural Equation model (SEM) was used for model verification. Results revealed that when considering on structural model of confirmatory factors of Women Empowerment (WE) and Psychological State (PS) were able to explain the variation of endogenous factors of Inspiration of Public Mind (IPM) to cause Environmental Conservation Behaviors (ECB) at 85.00 percent. Moreover, confirmatory factors of WE was able to explain the variation of IPM at 75.00 percent.